Evaluation of the dynamics of fattening of lactating cows of the newly created Ukrainian red dairy breed - Liliya Roman; Olena Bezaltychna; Serhiy Vyrvykyshka; Artem Iovenko; Tetyana Pushkar (Наукові горизонти)
The purpose of this study was to determine the dynamics of fattening of lactating cows of the newly created Ukrainian red dairy breed during the current lactation and at different lactation ages by eye assessment. Based on an industrial dairy complex-reproducer for breeding cattle of the Ukrainian red dairy breed, a scientific and industrial study was conducted to assess the dynamics of fattening of lactating cows (n=391) using a modified eye-measured scoring scale and an innovative methodological Model Cow approach to comparing the findings with the visualisation. The study employed structural-comparative, analytical, and statistical methods. The findings of this study revealed that lactating cows of the newly created Ukrainian red dairy breed had a steady downward trend in fertility rates compared to the optimum levels recommended by experts. Thus, the fatness of the first-born cows was on average 35.35-58.25% lower than the recommended level, of the second lactation cows – 18.91–25.67%, and of the third lactation cows – 21.82-28.33% (P < 0.001). In cows of the fourth and older lactations (4.43 lactations on average), the dynamics of fattening dynamics was closer to the recommended optimum indicators throughout the current lactation. On average, in the middle of lactation (134.96 days, n = 59), the fattening was 2.39 points, which was 89.91-79.67% of the recommended levels (P < 0.001). According to the observations during the current lactation, it was found that the fattening of lactating cows did not have time to reach optimum levels at the end of the lactation period, which indicated significant metabolic disorders in the body of females, especially of young age, which require finding ways to correct the system of feeding the dairy herd of the newly created breed. An innovative approach to assessing the fatness of dairy cows revealed the potential of the methodology to use research findings to regulate herd management and feeding behaviour of cows under intensive milk production technology